A Page and Its Politics: Situating Kullinā Khālid Sa'īd in Egypt's Ideological Landscape at the Time of Revolution'. Issue 2 (31st December 2020) - Woltering, Robbert; Abdulla, Rasha; Poell, Thomas; Rieder, Bernhard; Zack, Liesbeth
Abstract: In discussions concerning the importance of social media in the 25January revolution, a central role is given to the "Kullinā Khālid Sa'īd" [We're all Khaled Said] Facebook page. Using an advanced data collection and extraction application called Netvizz, a research team consisting of Arabists and Media studies specialists has collected and analysed all of the posts and comments exchanged through the page. This data set allows for a systematic analysis of the page. This article offers an outline of the ideological nature of "Kullinā Khālid Sa'īd, " with particular emphasis on the "revolutionary" period between 1 January – 11 February 2011. It argues that the page shows no evidence of political bias in the sense of explicit favoring of a political group. Rather, the page constituted a community of users who abstained from using politically factional language. Reflecting the mood and concerns of the revolution's grassroots masses, it clearly illustrates the disinclination to engage with formal politics.